Preparation and characterization of polyethylene glycol/chitosan composite water-based wound healing lubricant - Gao, Li; He, Xinyi; Zhang, Taohong; Li, Peipei; An, Ruifang (Frontiers in Bioengineering and Biotechnology, 2022)
The proportion of pregnant women giving birth through cesarean section is increasing annually worldwide. However, post-cesarean section scar diverticulum is a common condition that occurs and requires better surgical strategies than the methods currently used. We hypothesized that using biological lubricant topically on the incision area during C-section could be an option to minimize the scar. This water-based polyethylene glycol (PEG)/chitosan (CS) composite lubricant was prepared via ultrasonic blending. The product was characterized using scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, and Raman spectroscopy. The thermal stability of the materials and their heat absorption and release during heating were analyzed using thermogravimetric analysis and differential scanning calorimetry. Tribological tests proved that the PEG/CS composite had a better lubrication effect than either the PEG or CS lubricant alone, and the cell viability experiments verified that it had good biocompatibility. Finally, application of the composite lubricant onto the backs of mice modeling full-thickness skin incisions further confirmed that the product improved both the re-epithelialization and the collagen levels of the wounded skin. In conclusion, we expect our newly formulated PEG/CS composite lubricant to be useful not only for managing post-cesarean section scar diverticulum but also for healing skin wounds in general.